Peran Kepala Sekolah Dalam Pembelajaran Kolaboratif Guru - Setyawanto, Agus; Hariyadi, Bachtiar; Tontowi, Tontowi (Universitas Yudharta Pasuruan, 2023)
Teacher collaborative learning is an important way to improve teachers' skills. Teachers need to be supported by principals to participate in such activities. This study explores the role of principals in supporting teachers in collaborative learning policies. Data were collected from 518 teachers and eight principals in 24 primary schools in Surabaya City and Sidoarjo District. Data analysis used statistics for quantitative data and thematic analysis for qualitative data. The results show that principals provide strong support for teachers to engage in collaborative learning. They recognize the complexity of collaborative learning and the need to apply various leadership approaches. Collaborative learning tends to occur in professional communities, mentoring and joint collaborative events, although it still uses traditional methods. The research recommends that Indonesian schools adopt more modern forms of collaborative learning and update existing approaches to suit current needs.